A systematic review and meta-analysis of sleep hygiene implementation and its effect on sleep quality and fatigue in patients undergoing hemodialysis - Fauziah, Hesti Fathan Nurfais; Rochmawati, Erna; Padela, Aasim (Jurnal Ners, 2024)
Introduction: The prevalence of patients undergoing hemodialysis who experience sleep disturbances and fatigue is high. Pharmacologic management has consequences and adverse effects, therefore, integrative intervention is important to be investigated. Sleep hygiene is one such integrative intervention that improves comfort including enhancing sleep quality and reducing fatigue. However, none have synthesized the effect of sleep hygiene intervention, particularly in the hemodialysis setting. This systematic review aims to synthesize the effectiveness of sleep hygiene in improving sleep quality and fatigue in patients undergoing hemodialysis. Methods: This is a systematic review and meta-analysis of randomized controlled trials and quasi-experimental studies. Relevant studies were gathered by searching five databases from 2008-2023 using several keywords, such as sleep hygiene, sleep quality and fatigue. Quality assessment was conducted using relevant tools from the Joanna Briggs Institutes (JBI). Following that, synthesis of research findings was conducted using Review Manager version 5.4. Results: Seven studies of 3,633 screened were included, with one high-quality study (88%) and six studies of moderate quality (61-76%). The review indicated a significant difference in sleep quality (MD = -2.36; 95% CI = -4.28, -0.44; p=0.016). However, there was no significant difference in fatigue (SMD = -0.08; 95% CI = -0.40, 0.24; p=0.61). Conclusions: The evidence supports that sleep hygiene is effective in enhancing sleep quality. This systematic review contributes evidence to support the inclusion of sleep hygiene into holistic nursing to assist patients in improving sleep quality and reducing fatigue.